A review of the National Payment Systems ecosystems in South Africa, Kenya and Nigeria - Davids, Saarah (Graduate School of Business (GSB), 2025)
Remittances are a critical financial connection between migrant workers and their families back home. They contribute to Sustainable Development Goals (SDGs) like reducing inequality and ending poverty, while aligning with the objectives of South Africa's National Development Plan, which seeks to foster economic growth, financial inclusion, and regional integration. This dissertation examines the cost elasticity of remittance flows between South Africa and 11 sub-Saharan African countries from 2011 to 2023, focusing on how changes in remittance costs influence the volume of remittances sent. Panel regression analysis reveals a significant negative relationship between remittance costs in South Africa and remittance outflows to 11 SSA countries, particularly for smaller transfer amounts. Specifically, a moderate statistically significant negative correlation between the remittance cost of sending USD $200 and the personal remittance received. This indicates that an increase in remittance costs results in a decrease in the remittance volumes, supporting cost elasticity and the Law of Demand. The variability of remitting $500 is less than remitting $200, indicating that it is cheaper for migrants to remit at larger amounts due to lower transaction costs. However, remittance behaviour suggests inelastic demand: while costs increases, the remittance inflows decrease however not drastically. Regression analysis results show that an increase in the transaction costs results in a steady decline in volumes, while descriptive statistics suggest variations across the different South Africa-SSA corridors. Additionally, results indicate a statistically negative relationship between remittance inflows and GDP of the home country, indicating both influence remittance behaviour. This means that with a higher income in the home country, there is less reliance on remittances. Higher GDP per Capita in both sending and receiving countries is associated with higher remittance costs, suggesting income-related pricing trends. The study highlights how lower remittance costs can contribute to financial inclusion, economic growth, and poverty reduction and empower household savings, and is consistent with National Payment System's Vision 2025 of the South African Reserve Bank and policies such as the Conduct of Financial Institutions (COFI) Act. The findings underscore the need for targeted policy interventions aimed at fostering competition, innovation and cost effectiveness to reduce remittance costs and improve financial access, to promote equitable economic participation and supporting broader development objectives in the region.